(untitled) (Scientific journal of the Fergana State University, 2024)
This article covers the development of preschool children’s speech and ensuring the effectiveness of preparation for school education through an integrative approach to this process. The initial stage of the child’s introduction to social life is naturally not easy. Because the child goes beyond the narrow circle consisting only of parents and enters the life of the community. This process has different effects on children with different individual characteristics. Based on the child’s physical and mental characteristics, the article describes how to accustom him to a social lifestyle and form the skills to live freely in a community.